1999
DOI: 10.1073/pnas.96.4.1315
|View full text |Cite
|
Sign up to set email alerts
|

The retinitis pigmentosa GTPase regulator, RPGR, interacts with the delta subunit of rod cyclic GMP phosphodiesterase

Abstract: Recently, the retinitis pigmentosa 3 (RP3) gene has been cloned and named retinitis pigmentosa GTPase regulator (RPGR). The amino-terminal half of RPGR is homologous to regulator of chromosome condensation (RCC1), the nucleotide exchange factor for the small GTPbinding protein Ran. In a yeast two-hybrid screen we identified the delta subunit of rod cyclic GMP phosphodiesterase (PDE␦) as interacting with the RCC1-like domain (RLD) of RPGR (RPGR 392 ). The interaction of RPGR with PDE␦ was confirmed by pull-down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 41 publications
1
85
2
Order By: Relevance
“…Since RCC1 domains may have guanine nucleotide exchange factor activity for small GTPases such as Ran [Bischoff and Ponstingl, 1991] or ARF1 and Rab proteins [Rosa et al, 1996], it was postulated that RPGR may also be an exchange factor for an unknown GTPase. Yeast two hybrid studies identified two proteins interact- ing with the RCC1 domain of RPGR: the phosphodiesterase delta subunit (PDE δ) [Linari et al, 1999a;Hong et al, 2001] and a novel protein called RPGRIP1 [Boylan and Wright, 2000;Roepman et al, 2000;Hong et al, 2001]. Interestingly, PDEδ not only interacts with retinal phosphodiesterase subunits [Florio et al, 1996], but also with the small GTPases Rab13 [Marzesco et al, 1998] and Arl3 [Linari et al, 1999b].…”
Section: Biological Relevance Mutations In the Rcc1-like Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Since RCC1 domains may have guanine nucleotide exchange factor activity for small GTPases such as Ran [Bischoff and Ponstingl, 1991] or ARF1 and Rab proteins [Rosa et al, 1996], it was postulated that RPGR may also be an exchange factor for an unknown GTPase. Yeast two hybrid studies identified two proteins interact- ing with the RCC1 domain of RPGR: the phosphodiesterase delta subunit (PDE δ) [Linari et al, 1999a;Hong et al, 2001] and a novel protein called RPGRIP1 [Boylan and Wright, 2000;Roepman et al, 2000;Hong et al, 2001]. Interestingly, PDEδ not only interacts with retinal phosphodiesterase subunits [Florio et al, 1996], but also with the small GTPases Rab13 [Marzesco et al, 1998] and Arl3 [Linari et al, 1999b].…”
Section: Biological Relevance Mutations In the Rcc1-like Domainmentioning
confidence: 99%
“…The effect on these interactions of a growing number of missense mutations in the RCC1 domain, many of which affect conserved residues, should be tested [Linari et al, 1999a;Boylan and Wright, 2000;Roepman et al, 2000].…”
Section: Biological Relevance Mutations In the Rcc1-like Domainmentioning
confidence: 99%
“…Interactions with prenylated small GTPases of the Ras superfamily (12,(14)(15)(16), with a prenylated prostacyclin receptor, a G proteincoupled receptor located on blood vessels (17), as well as with nonprenylated small GTPases (Arl2 and Arl3) (18) are well established, but the physiological significance of these interactions is largely undefined. In the retina, PrBP/␦ was shown to interact in vitro with the RCC1-like domain of the retinitis pigmentosa G protein regulator (RPGR) (19,20), the prenyl chains of rhodopsin kinase (GRK1) (10), and PDE6␣ and PDE6␤ subunits (10,13).…”
mentioning
confidence: 99%
“…PDE6D (also known as PDEd and PrBP) is a prenylbinding protein involved in ciliary targeting of prenylated proteins [1][2][3][4]. Previous studies uncovered that PDE6D interacts with RPGR [5,6], mutations of which cause retinitis pigmentosa [7][8][9][10]. More recently, the structure of the PDE6D and RPGR (the N-terminal half) complex was determined and RPGR was proposed as a scaffold protein that recruits cargo-loaded PDE6D to the ciliary base [6].…”
mentioning
confidence: 99%